2009
DOI: 10.2175/193864709793846349
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanistic Principles and Proposed Modeling Approach for Waste Activated Sludge Reduction Technologies

Abstract: WERF's 05-CTS-3 Evaluation of Processes to Reduce Activated Solids Generation and Disposal aims to establish a comprehensive evaluation methodology for waste activated solids (WAS) reduction processes based on the in-depth consideration of a select number of technologies considered to be representative of the many options currently available in the marketplace. These technologies cover both those intended to reduce the generation of wastewater treatment residuals from the liquid process, as well as those desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It is reported that the flash reaction causes rupture of the cell, thus the step is important for sufficient hydrolysis to occur (Whitlock et al, 2009). Gurieff et al (2011) compared both batch and continuous thermal hydrolysis using the Biothelys and the Exelys process and found that the solubilization of COD and VSS were similar for both processes, with slightly better results for the continuous process, indicating that effective hydrolysis occurred with both processes.…”
Section: Figure 3: Process Flow Schematic Of An Exlyse Thermal Hydrolmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the flash reaction causes rupture of the cell, thus the step is important for sufficient hydrolysis to occur (Whitlock et al, 2009). Gurieff et al (2011) compared both batch and continuous thermal hydrolysis using the Biothelys and the Exelys process and found that the solubilization of COD and VSS were similar for both processes, with slightly better results for the continuous process, indicating that effective hydrolysis occurred with both processes.…”
Section: Figure 3: Process Flow Schematic Of An Exlyse Thermal Hydrolmentioning
confidence: 99%
“…The type of solids and thus the amount of ammonia expected in the digestion process is the limiting parameter regarding the percent solids feed to digestion. The drastic changes in solids rheology with a significantly reduced viscosity allows proper mixing at high solids contents with typical digestion mixing equipment (Whitlock et al, 2009). Feeding MAD at a higher solid content allows significant reduction in digestion volume requirements thus providing significant capital savings since construction of new digesters, which is a major capital investment, may be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…! 16 After 20-30 min hydrolyzing treatment, the sterilized sludge is pumped to the flash tank, where the rupture of the cells occurs due to the fast pressure drop [51]. Generally, the sludge from the flash tank is too hot to feed a mesophilic digester and it needs to be cooled to 42-44 °C by heat transfer.…”
Section: Thermal Pretreatmentsmentioning
confidence: 99%
“…Specifically, when the sludge enters the flash tank, the water contained in the flocs and inside the cells partially vaporizes, resulting in their structure damaging. Thus, the presence of the flash tank seems to be important for a sufficient hydrolysis of the sludge [51,[53][54][55]. On the other hand, some studies highlighted that flash tank may not result to valuable differences in terms of COD and VSS solubilization !…”
Section: Thermal Pretreatmentsmentioning
confidence: 99%
“…This maximizes the yield of digestion intermediates readily consumed by anaerobic biota, which in turn increases the production of biogas and increases the potential for CHP generation. Recent research conducted by the Water Environment Research Foundation (Whitlock, Sandino, Novak, Johnson, and Fillmore 2009) indicates significant improvements in the dewatering characteristics of the stabilized biosolids as a result of these preconditioning steps. Some of these processes and technologies have been demonstrated in the laboratory and at the pilot scale while others have been installed at operating treatment plants.…”
Section: Pretreatment Of Wastewater Residual Solidsmentioning
confidence: 99%